Exploring the medicine cost of managing Diabetes Mellitus in Nepal: A cross-sectional analysis of oral hypoglycaemic medications. - Rajeev Shrestha; Amrita Aryal; Asmita Priyadarshani Khatiwada; Shreya Dhungana; Sunil Shrestha (PLoS ONE)
Diabetes Mellitus is a significant global public health burden. Although medication adherence is an inevitable consideration in managing and curing the disease, medication price is the major barrier to patients in Nepal, like any other low- and middle-income countries. Prescribing in brand-name inhibits the possibility of accessing cost-effective generic alternatives in Nepal. This study aimed to explore and examine price variations among the oral hypoglycaemic medicines (OHMs) available in the country and their distribution in various medicine-related characteristics. A cross-sectional study was conducted using a convenient sample of five tertiary care hospital pharmacies in Kathmandu, publicly accessible online pharmacy websites, and a government database to list the OHMs available in Nepal. The study determined price variations and statistically tested the association between these variations and the characteristics of the medicines. Fourteen OHMs were available as 57 generic medicine items with different formulations in Nepal. The maximum of 484.82% of price variation was found. Fourteen, fifteen and eighteen OHMs have variations of over 100%, more than 10 rupees and no price change, respectively. Except for Dipeptidyl Peptidase-IV (DPP-4) Inhibitors and Thiazolidinediones (TZDs), all other categories of OHMs have >100% of price variation in medicine items. Although Nepal itself produces most of the available OHMs, the available OHMs have price variations. Most fixed dose combinations showed no reduction in cost compared to their component medicine's mean price. This study presented and discussed the price variation scenario of OHMs with their medicine-related characteristics to develop and implement effective drug policies and programs that can address medication price-related issues to ensure access to OHMs without placing an economic burden on patients.